Tunning self-assembled phases of bovine serum albumin via hydrothermal process to synthesize novel functional hydrogel for skin protection against UVB - Yadav K.; Das M.; Mishra N.K.; Chhabra A.; Mishra A.; Srivastava S.; Sharma P.; Yadav S.K.; Parmar A.S. (My University, 2025)
Ultraviolet rays - B (UVB) can be efficiently absorbed by the cellular molecules of skin inducing damage within skin cells and a major cause of melanoma cancer. In recent years, several studies have reported the adverse effects of traditionally used organic and inorganic material-based sunscreens and UVB blockers. In this study, bovine serum albumin (BSA) has been used as a precursor to synthesize temperature- and pressure-dependent phase transition from sol (globular aggregates) - gel (hydrogels) - sol (carbon quantum dots) using a single-step hydrothermal method with an objective to develop an efficient and effective UVB blocker. The synthesized hydrogels exhibit UV - attenuation, self-fluorescence, and high biocompatibility properties that make them a suitable candidate for UV-blocker or sunscreen material. The biological efficacy of the hydrogels was studied through cyto-toxicity studies. Also, UVB blocking efficiency of developed hydrogel in primary mice skin cell culture as well as in vivo in mice model was studied. In vivo study on mice further demonstrated prominent thickening of stratum corneum and epidermis with perivascular edema in the dermis after 5 days of UVB exposure. Hence, this suggesting that hydrogel could be a potential candidate for protecting the skin from UVB exposure and reducing the threat of skin cancer. © 2022 Kanchan Yadav et al., published by De Gruyter.